A Blended Approach to Reading and Writing Graphic Stories. (25th October 2013) - Brown, Sally
Abstract: This article documents the experiences of a diverse group of second grade students during a nine week unit of study focused on graphic stories. The project begins as the class is immersed in reading graphic stories designed for young readers. Images, written text, and dialog are utilized to scaffold reading comprehension and to practice fluency. Then, students construct their own graphic stories based on characters from books, popular culture, and personal experiences. Each story is transformed into a digital format with narration using Photo Story. The results indicate student growth in the areas of comprehension and fluency. There is also a need to integrate new literacies with traditional to prepare students for communicating in the 21st century.